Fresno County Women Lawyers/Fresno County Bar Association Seminar on Judicial Selection Held at Ramada Inn - Watkins, Howard::::::::: (1989)
Terrence Flanagan, Judicial Appointments Secretary to Governor George Deukmejian, speaking